Peningkatan Kualitas Produk Pindang Berbasis Ekspektasi Konsumen Di Kabupaten Ogan Ilir - Karo Karo, Pelliyezer (Jurnal Akademi Pariwisata Medan, 2025)
This research was conducted as a deepening of previous research results related to consumer perceptions of pindang products. The research is qualitative in nature and was carried out in an experimental form in three stages and a participatory approach method, namely (1) inducing research results to informants/participants, (2) providing assistance and experimentation on pindang products according to consumer expectation findings, (3) and conducting deep interview evaluations on product quality and consumer feedback. The research aims to provide new insights for the informants, who are members of the community/managers of restaurants and eateries in Ogan Ilir Regency, regarding the quality of pindang products. The research shows significant changes in the management of pindang products, both Pindang Pegagan and Pindang Meranjat. Consumers have responded positively to the results of the pindang products with the new management that has been implemented. An increase in sales potential has occurred and the selling value has improved, but further research is needed on this matter through quantitative data findings. In the final stage, the informants agreed to create a distinctive regional culinary image from the produced pindang. In the long term, success will certainly make an attraction for the culinary marketing of Ogan Ilir, which will impact the growth of tourist visits.